2014
DOI: 10.5194/cp-10-1363-2014
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Holocene hydrological changes in the Carpathian–Balkan region using speleothem δ<sup>18</sup>O and pollen-based temperature reconstructions

Abstract: Abstract.Here we present a speleothem isotope record (POM2) from Ascunsȃ Cave (Romania) that provides new data on past climate changes in the Carpathian-Balkan region from 8.2 ka until the present. This paper describes an approach to constrain the effect of temperature changes on calcite δ 18 O values in stalagmite POM2 over the course of the middle Holocene (6-4 ka), and across the 8.2 and 3.2 ka rapid climate change events. Independent pollen temperature reconstructions are used to this purpose. The approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 65 publications
(113 reference statements)
3
50
0
Order By: Relevance
“…Consequently, climate reconstructions using δ 18 O-climate relationships in various sedimentary archives (e.g., speleothems) have difficulties distinguishing between changes in local climate and/or shifts in climatic influences that could be interpreted as changes in climate variables. Romania has a very diverse karst landscape, offering a great potential for reconstructing past climate based on cave deposits (Constantin, Bojar, Lauritzen, & Lundberg, 2007;Drăguşin et al, 2014;Onac et al, 2015;Onac, Constantin, Lundberg, & Lauritzen, 2002;Tămaş, Onac, & Bojar, 2005). However, there are only a few studies available which documented the rainwater δ 18 O variability and corresponding cave dripwater changes in the region (Drăguşin et al, 2017;Perşoiu, Onac, Wynn, Bojar, & Holmgren, 2011), making the climatic interpretation of speleothem δ 18 O from this region ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, climate reconstructions using δ 18 O-climate relationships in various sedimentary archives (e.g., speleothems) have difficulties distinguishing between changes in local climate and/or shifts in climatic influences that could be interpreted as changes in climate variables. Romania has a very diverse karst landscape, offering a great potential for reconstructing past climate based on cave deposits (Constantin, Bojar, Lauritzen, & Lundberg, 2007;Drăguşin et al, 2014;Onac et al, 2015;Onac, Constantin, Lundberg, & Lauritzen, 2002;Tămaş, Onac, & Bojar, 2005). However, there are only a few studies available which documented the rainwater δ 18 O variability and corresponding cave dripwater changes in the region (Drăguşin et al, 2017;Perşoiu, Onac, Wynn, Bojar, & Holmgren, 2011), making the climatic interpretation of speleothem δ 18 O from this region ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Summer and autumn thermal anomalies seem to be connected to decadal-scale variability known as Atlantic Meridional Oscillation (AMO) (Ionita et al, 2013). Therefore, CE Europe and especially the Carpathian region are considered sensitive to hydrological forcing (Drăguşin et al, 2014;Finsinger et al, 2014;Gałka et al, 2016). Providing additional palaeoenvironmental data from this region will lead to better constraining the spatial and temporal variability in hydroclimatic gradients between west-east and north-south Europe at the Holocene scale (Davis and Brewer, 2009;Davis et al, 2003;Magny et al, 2013;McDermott et al, 2011;Roberts et al, 2012;Drăguşin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results for the period prior to April 2013 were reported by Drȃguşin et al (2014). Calcite farmed after this period was measured at CEA-CNRS-LSCE (France) on a VG-OPTIMA mass spectrometer.…”
Section: Modern Calcite Stable Isotopesmentioning
confidence: 99%
“…Nevertheless, by analyzing δ 18 O data from stalagmite POM 2, Drȃguşin et al (2014) demonstrated that this stalagmite recorded during the Holocene millennial scale hydrological changes that took place in the eastern Mediterranean. This suggests that calcite at Ascunsȃ Cave is continuously deposited under different climate settings, thus making speleothems from this cave useful for the study of past atmospheric circulation (Cruz et al, 2006;Lachniet, 2009 (Baldini et al, 2006;Dreybrodt and Scholz, 2011).…”
Section: Relevance For Speleothem Paleoclimate Studiesmentioning
confidence: 99%
See 1 more Smart Citation